Avaliação do retardamento do desenvolvimento de plântulas de espécies arbóreas nativas - Banci, André Moisés (Universidade Federal de São Carlos, 2013)
Due to the high rates of environmental degradation and their consequences to the population, environmental recovery in many areas is an urgent need. Recovering degraded areas may be done by using several techniques alone or in combination. The traditional recovery system by means of seedling planting is expensive and has limited guarantee of germination using no-tillage sowing. Therefore, this study tested the viability of experimentally growing seedlings from seven native tree species without them suffering significant changes, after storing the sprouts in cold chambers for periods ranging from 7 to 28 days. The results showed that it is possible to delay the growing of radicles in seedlings stored in cold chambers (15°C) when compared to seedlings stored in germinator (25°C). In four out of seven species (Marlierea eugeniopsoides, Cordia americana, Cedrela fissilis e Hymenaea courbaril) stored for 14 days in cold chambers, the seedlings survival rates were higher than 77% 60 days after they were seeded in the nursery containers. This survival rate was similar to the rate of seedlings not stored in cold chambers. In three species (Marlierea eugeniopsoides, Luehea grandiflora e Hymenaea courbaril) stored for 21 days the survival rates were higher than 75%. The species Marlierea eugeniopsoides did not show significant survival changes even after storage in cold chamber for 28 days.
Assessing delayed growth and survival of seedlings from native tree species stored under low temperature
Keywords: Reflorestamento; Plantas - desenvolvimento; Ecologia de restauração; Crescimento de plântulas; Viveiros; Câmara fria; Delayed growth; Recovery technique; Seedlings; Cold chamber; Nursery; CIENCIAS BIOLOGICAS::ECOLOGIA